Evaluating the Impact of Drought on Palm Oil Productions in Malaysia: Insights for Agricultural Modernization - Md Salehan, Halimatun Saadiah (Journal of Statistical Modeling and Analytics (JOSMA), 2025)
This study investigates the impact of drought on palm oil production in Malaysia, focusing on Melaka. Using the six-month Standardized Precipitation-Evapotranspiration Index (SPEI-6), it quantifies drought severity and its influence on yields. Malaysia, as a major palm oil producer, faces challenges from climate variability, particularly during dry periods. Statistical analysis reveals a correlation coefficient (R) of 0.725, demonstrating a strong positive relationship between SPEI-6 values and palm oil yields, where wetter conditions correspond to higher yields. The study evaluates the effects of six-month drought intervals, detailing the statistical models and variables analyzed. These findings highlight patterns that can enhance agricultural resilience and resource management in the palm oil sector, particularly in Melaka. By addressing climate-related vulnerabilities, this research provides actionable insights for mitigating climate impacts and strengthening adaptive strategies within Malaysia’s key agricultural sectors.